Complete testicular remission after chemotherapy in a patient with advanced seminoma: is the testicle a real 'sanctuary'? A case report and review of the literature. Issue 5 (15th February 2021) - Caspani, Francesca; Nigro, Olga; Ogliari, Francesca Rita; Proserpio, Ilaria; Dehò, Federico; Capogrosso, Paolo; Valdatta, Luigi; De Palma, Diego; Garutti, Leonardo; Tamborini, Federico; Chini, Claudio
Abstract : Testicular cancer is relatively uncommon, but at the same time, it is the most common solid tumor in men between the ages of 20 and 34 years. Seminoma represents the most frequently encountered germ cell tumors. Because orchiectomy is usually performed before chemotherapy, little is known about the effect of systemic chemotherapy on primary testicular tumors. Furthermore, the testis has always been considered a sanctuary site, an immune-privileged site in which inadequate exposure of the tumor to chemotherapy may occur. We report the case of a young patient with advanced seminoma with a complete testicular response after four cycles of cisplatin-based chemotherapy. Then, we performed a systematic review of the literature reporting the studies published to date on the topic.